Investigating the problem of misdiagnosis in model-based fault diagnosis - Kościelny, Jan Maciej; Bartyś, Michał (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with one partly unconscious property of the model-based diagnosis. It discusses occasional contradictions between diagnoses that are logically correct but, in fact, are not consistent with the physical state of the system being diagnosed. This property is studied and discussed based on the analysis of diagnoses generated by four selected approaches using binary and trivalent diagnostic signals.
Keywords: diagnostic reasoning; misdiagnosis; fault isolation; fault distinguishability